Caracterización eléctrica del sistema Co3O4 + PVOH mediante el uso de la técnica de espectroscopia de impedancia compleja (IS) en altas temperaturas - Saldarriaga Agudelo, Wilmer de Jesus; Buendia, Melisa; Zapata Sanchez, Victor Hugo (Revista Científica, 2018)
<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Results in impedance spectroscopy show high values in electrical conductivity (10<span style="font-size: 7.199999999999998pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: super; white-space: pre-wrap;">-3<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">-10<span style="font-size: 7.199999999999998pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: super; white-space: pre-wrap;">- 4<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> S / cm) in Co<span style="font-size: 7.199999999999998pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: sub; white-space: pre-wrap;">3<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">O<span style="font-size: 7.199999999999998pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: sub; white-space: pre-wrap;">4<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> + PVOH samples, with sweeps temperature between 80 and 200 <span style="font-size: 12pt; font-family: Symbol; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">°<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">C, this indicate a strong structural bond between the ions of Co<span style="font-size: 7.199999999999998pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: super; white-space: pre-wrap;">3+<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Co<span style="font-size: 7.199999999999998pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: super; white-space: pre-wrap;">2+<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> and its surroundings with the system, finding activation energy <span style="font-size: 12pt; font-family: Symbol; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">∼<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> 1.13 eV for the cobalt ion, adjusting by means of the Arrhenius model. The frequency sweeps show a dynamic behavior reflected in the graphs of the imaginary part of the electrical module and the impedance between 42 Hz and 5 MHz, allowing the adjustment and data analysis of a RC circuit with order of capacitance values of 10<span style="font-size: 7.199999999999998pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: super; white-space: pre-wrap;">-9<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> nF. The results of the conductance frequently show a behavior that obeys the universal law of relaxation of Jonscher (<span style="font-size: 12pt; font-family: Symbol; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">σ<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> = <span style="font-size: 12pt; font-family: Symbol; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">σ<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">dc + α ω<span style="font-size: 7.199999999999998pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: super; white-space: pre-wrap;">n<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">) with values obtained for the exponent n (0,7<span style="font-size: 12pt; font-family: Symbol; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">•<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> n <span style="font-size: 12pt; font-family: Symbol; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">•<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> 1), also the graphs of the Peak relaxation frequency <span style="font-size: 12pt; font-family: Symbol; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">ω<span style="font-size: 7.199999999999998pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: sub; white-space: pre-wrap;">p<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #212121; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> vs. Temperature shows a process thermally activated with the same energy of ion activation.